Seabiscuit [videorecording (DVD)] - Ross, Gary, 1956-; Maguire, Tobey, 1975-; Bridges, Jeff, 1949-; Cooper, Chris, 1951-; Banks, Elizabeth, 1974-; Stevens, Gary, 1963-; Macy, William H., 1950-; DuCoeur, Kingston; Jones, Eddie, 1940-2019; Hillenbrand, Laura (Universal, 2003)
Based on a true story. A half-blind ex-prizefighter and mustang breaker team up with a millionaire and his rough-hewn, undersized horse, Seabiscuit. The men bring Seabiscuit to incredible heights, helping to turn a long shot into a legend. Eventually, Seabiscuit earns Horse of the Year honors in 1938.